“Análisis del flujo de efectivo en tiempos de Covid y Post Covid en la compañía de transporte escolar e Institucional Comtresin S.A.” - Chuchimbo Changoluisa, Stalin David (2024)
The main objective of this study was to examine the behavior of cash flow in the School and Institutional Transportation Company COMTRESIN S.A. in the context of the pandemic and its subsequent recovery (2020 - 2022). To achieve this, a research methodology of quantitative approach was used, being documentary, bibliographic, and supported with interviews; using the descriptive, deductive, and explanatory method, to understand how the company has managed its cash flow, adapting to the changing conditions of the environment. The analysis of the company's financial data was included, to measure its efficiency in cash management. In general terms, it was observed that the company had successful management of its cash flow during the pandemic, whose most critical period was 2021; the strategies implemented of not getting into debt in the first two years, together with the good track record in the management of payments, were key to recover in the post-COVID period. It is noteworthy that operating revenues did not decline as might be expected, which means that the company was able to adapt to the situation, taking measures such as optimizing its services and routes to improve its cash flow. In the post-COVID phase, already in 2022, net operating cash flow grew by 1905.49%, reflecting the recovery of the company's operations. Accumulated cash tripled in value concerning the previous period and net income increased by 587.05%, reflecting a direct relationship between them. Liquidity or current ratio, immediate liquidity, and working capital grew in 2021, a scenario that changed in 2022 for the first two indicators, as they decreased by 75.86% and 55.95%, respectively, which occurred because debts grew significantly, although they remained positive